Elucidating the determination of the rosette galls induced by Pisphondylia brasiliensis Couri and Maia 1992 (Cecidomyiidae) on Guapira opposita (Nyctaginaceae) - Fleury, Graziela; Ferreira, Bruno G; Soares, Geraldo L. G; Oliveira, Denis C; Isaias, Rosy M. S (Australian journal of botany, 2015)
The modulation of plant development has been the focus of research on insect galls because galling insects induce distinct shapes to acquire the same necessities, shelter and food. Due to the variety of gall morphotypes, it can be assumed that the key processes for their development rely on plant cells’ morphogenetical potentialities. In the present study we investigated the rosette bud galls induced by Pisphondylia brasiliensis on Guapira opposita to check whether two morphogenetical pathways – the shortening of the internodes and the over differentiation of axillary buds – are independent or whether they are concomitant events towards the morphogenesis of the galls. Biometrical measures were made to test whether the final size of the galls is correlated with the number of inducers per gall. We noted that two patterns of activity were observed in gall meristems: the first differentiated pairs of leaves with opposite phyllotaxy, and the other differentiated new buds at the base of each leafy projection, with the development of sequential leafy projections, in a disorganised phyllotaxy. This second pattern repeated until gall maturation, when a master cambium, typical of the Nyctaginaceae, differentiated in larger galls. The two morphogenetical pathways occurred concomitantly, leading to the overproduction of leafy projections. Cell responses at gall development site produce mechanical protection to P. brasiliensis individuals. The larger galls have the higher number of inducers, and the coalescence of galls allows an increase in gall size by precociously triggering the master cambium activity, a developmental peculiarity of G. opposita uncommon for Cecidomyiidae galls.